Academic and gender predictors of L2 listening proficiency: A quantitative study in Croatian higher education - Ana Penjak; Nevenka Maras (Universitas Syiah Kuala, 2026)
Listening is a crucial receptive skill in second language (L2) acquisition, but its development is not uniform and may be shaped by both academic and learner-related factors. Building on this perspective, the present study investigates whether academic background and gender influence listening comprehension in the higher education context. A sample of 120 students (F = 58, M = 62) from a public university in Croatia completed an adapted listening performance test alongside a background questionnaire addressing educational history and language-learning experience. ANOVA and t-test results showed that the final English grade significantly predicted listening performance (F = 45.61, p < 0.01, ηp² = 0.54), indicating a strong relationship between prior academic achievement and listening ability. Secondary education background also had a significant effect on listening outcomes (t = −2.26, p = 0.03, Cohen’s d = 0.43). In contrast, gender (p = 1.00, Cohen’s d = 0.00), international study mobility participation, and the number of English-medium courses attended showed no statistically significant effect. These findings highlight the importance of prior academic achievement and educational background in shaping L2 listening skills. In an English for specific purposes (ESP) perspective, results suggest that adapting listening instructions to students’ linguistic and educational profiles may enhance learning outcomes. Future research should explore additional factors such as listening strategies, metacognitive awareness, and exposure to authentic input, to further inform pedagogical design.